The relationship between selling strategy and sales performance among salespersons / Wan Shahrul Aziah Wan Mahamad...[et al.] - Wan Mahamad, Wan Shahrul Aziah; Saad, Ramli; Mukhta, Siti Aminah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Selling-strategy formulation is a critical dimension of sales performance effectiveness. As businesses become more optimistic towards opportunity growth, the pressure becomes higher for sales organizations to meet the higher revenue targets. For this reason, optimizing sales performance calls for a more rigorous and data driven approach to foundational sales processes, including sales strategies. Thus, this study aims to identify the relationship between sales performance and the independent variables (adaptive selling strategies, customer-oriented selling strategies, salesperson presentation skills selling strategies & relational selling strategies). As proposed, a simple random sampling was used and one hundred questionnaires were distributed to the salespersons working around Sunway Lagoon, Selangor, with eighty respondents giving the feedbacks. The findings of the research found that all the variables measured have significant relationships with the dependent variable and an adaptive selling strategy has the most influence on sales performance. The findings of the study are important for the sales organization improving their sales performance strategies.